Shrimp miR-1000 Functions in Antiviral Immunity by Simultaneously Triggering the Degradation of Two Viral mRNAs - Gong, Yi; Ju, Chenyu; Zhang, Xiaobo (Frontiers in Immunology, 2018)
MicroRNAs (miRNAs) function as crucial suppressors of gene expression via translational repression or direct mRNA degradation. However, the mechanism of multi-gene regulation by a host miRNA in antiviral immunity has not been extensively explored. In this study, the regulation of two white spot syndrome virus (WSSV) genes by its host (Marsupenaeus japonicus shrimp) miRNA (shrimp miR-1000) was characterized. The miRNA target gene prediction showed that only two virus genes (wsv191 and wsv407) might be the targets of miR-1000. The results of insect cell transfection assays revealed that shrimp miR-1000 could target multiple virus genes (wsv191 and wsv407). The mRNA degradation analysis and RNA FISH (fluorescence in situ hybridization) analysis indicated that miR-1000 triggered the mRNA degradation of target genes through 5’-3’ exonucleolytic digestion in vivo and thereby inhibited the virus infection in shrimp. The miRNA-mediated 5’-3’ exonucleolytic digestion of target mRNAs stopped near the 3’UTR (3’ untranslated region) sequence complementary to the seed sequence of miR-1000. Therefore, our study provided novel insights into how a host miRNA targeted multiple viral genes and prevented host from virus infection.